2010
DOI: 10.1177/0038040710392719
|View full text |Cite
|
Sign up to set email alerts
|

Parental Involvement and Students’ Cognitive Outcomes in Korea

Abstract: Studies of parental involvement and children’s education in a variety of contexts can provide valuable insights into how the relationships between parental involvement and student outcomes depend upon specific local contexts of family and education. Korean education is distinctive with its high prevalence of private tutoring, which not only imposes an economic burden on parents but also requires parents’ time and efforts to select the best kind of private tutoring for their children and to keep track of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(147 citation statements)
references
References 26 publications
8
118
0
9
Order By: Relevance
“…For example, Hannum's work showed that household income exerts a net net on children's school enrollment probabilities and education attainment in China (Hannum 2003). In addition, parents in Korea tend to spend their income on extracurricular education services, such as private tutoring, which prepares the children better academically (Park,Byun, and Kim 2011).…”
Section: Income and Parenting In The Chinese Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hannum's work showed that household income exerts a net net on children's school enrollment probabilities and education attainment in China (Hannum 2003). In addition, parents in Korea tend to spend their income on extracurricular education services, such as private tutoring, which prepares the children better academically (Park,Byun, and Kim 2011).…”
Section: Income and Parenting In The Chinese Contextmentioning
confidence: 99%
“…East Asian societies differ substantially from U.S. society both culturally and institutionally. Extending research to East Asian societies will thus yield clues about whether the observed relationship between family's characteristics and children's achievement is generalizable to wider social contexts (Park 2008;Park and Kim 2011). High scholastic and professional achievement in East Asian countries and among East Asian descendants in the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…In developing extrinsic motivation towards school learning, the formal role of achievements is emphasised and comparisons to the peer group are used in the process of motivating children to learn. Research conducted so far shows that the practices promoting child development undertaken by (Park, Byun and Kim, 2011). This issue has not been empirically resolved to date.…”
Section: Parental Involvement In Educating Children With Senmentioning
confidence: 98%
“…For South Korea, Shin (2013) identifies the importance of high levels of achievement motivation, fuelled both by the Confucian value placed upon scholarship and more instrumental career concerns, the proportion of time spent studying each week, and parental expectations and involvement. This latter factor has been emphasised as contributing towards a high degree of "educational zeal" (Sorensen, 1994, p.21) with parents spending considerable time selecting and monitoring private tutoring for their children (Bray, 2010;Park, Byun, & Kim, 2011). As Sorenson points out, the academic success of South Korean students is less a matter of curriculum, pedagogy or structural factors such as class size than the result of how education is embedded within the fabric of Korean society.…”
Section: Beyond Pedagogy: Factors Associated With High Achieving Counmentioning
confidence: 99%